Value of Dermatology Nights at a student-run free clinic. Issue 2 (4th March 2021) - Lin, Christine P.; Loy, Sydney; Boothe, William D.; Bennett, Kelly; Tarbox, Michelle B.; Prabhu, Fiona; Sturgeon, Ashley
Abstract: The Free Clinic at Lubbock Impact is a student-run free clinic affiliated with the Texas Tech University Health Sciences Center in Lubbock, Texas. Every Wednesday, the clinic provides free health services to the uninsured patient population of Lubbock and the surrounding West Texas regions. In addition to the weekly essential primary care services, "Dermatology Night" is held once a month for patients in need of dermatologic care. The study presents a cost analysis of the dermatologic procedures performed at The Free Clinic Dermatology Nights over a 2-year period from February 2018 through January 2020 using current procedural terminology codes and Medicare reimbursement rates. The dermatologic procedures performed in this time were valued at $8412.37. The study emphasizes the value of Dermatology Nights at a free clinic and reflects the dermatologic-specific needs of the uninsured Lubbock and West Texas patient population.